The impact of multiple sclerosis severity on health state utility values: Evidence from Australia. (July 2017) - Ahmad, Hasnat; Taylor, Bruce V; van der Mei, Ingrid; Colman, Sam; O'Leary, Beth A; Breslin, Monique; Palmer, Andrew J
Background: The measurement of health state utility values (HSUVs) for a representative sample of Australian people with multiple sclerosis (MS) has not previously been performed. Objectives: Our main aim was to quantify the HSUVs for different levels of disease severities in Australian people with MS. Method: HSUVs were calculated by employing a 'judgement-based' method that essentially creates EQ-5D-3L profiles based on WHOQOL-100 responses and then applying utility weights to each level in each dimension. A stepwise linear regression was used to evaluate the relationship between HSUVs and disease severity, classified as mild (Expanded Disability Status Scale (EDSS) levels: 0–3.5), moderate (EDSS levels: 4–6) and severe (EDSS levels: 6.5–9.5). Results: Mean HSUV for all people with MS was 0.53 (95% confidence interval (CI): 0.52–0.54). Utility decreased with increasing disease severity: 0.61 (95% CI: 0.60–0.62), 0.51 (95% CI: 0.50–0.52) and 0.40 (95% CI: 0.38–0.43) for mild, moderate and severe disease, respectively. Adjusted differences in mean HSUV between the three severity groups were statistically significant. Conclusion: For the first time in Australia, we have quantified the impact of increasing severity of MS on health utility of people with MS. The HSUVs we have generated will be useful in further health economic analyses of interventions that slow progression of MS.